Piedad de la Cierva in the rearguard of science and feminism: Echoes of a scientific woman - Zen, Giovanni; Morales, Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the Spanish feminist context of the 1930s, Piedad de la Cierva, a prominent Murcian scientist, did not belong to any feminist organization in struggle for women’s rights. However, she stood out thanks to her efforts and work. The aim of this article is to show how the Spanish scientist Piedad de la Cierva attained personal, scientific, and human goals, and how relevant and inspirational she can be for other past and present scientific women against society expectations and pressure. She can now be considered an example for women.